Effect of extrusion process on the stress corrosion cracking resistance of 7N01 aluminum alloy (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
In this work, the effect of extrusion process on the mechanical properties and the stress corrosion cracking (SCC) resistance of 7N01 aluminum alloys are systematically investigated by tensile testing, slow strain rate testing, electrochemical experiment, scanning electron microscopy(SEM), electron backscattered diffraction (EBSD) and transmission electron microscope (TEM) observation, respectively. The results show that with the increase of extrusion temperature, the SCC resistances are improved, and this tendency is also proved by the electrochemical experiments include polarization curves and EIS results. The Microstructure observation results reveal that recrystallization play an important role on the SCC resistances of the alloys: the new recrystallization grain boundaries with higher grain boundary energy and wider PFZ can magnify the difference of electrochemical property between grain boundary area and the grain interior, thus raises the stress corrosion crack sensitivity of the alloys.
Keywords: Stress corrosion cracking; Extrusion process; Recrystallization; Al-Zn-Mg alloys